Efektivitas Kinerja Guru dan Kepala Sekolah Dalam Kekompakkan Penyelesaian Konflik Sosial di Sekolah - Lailal Amna; Silfia Hanani (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
Moral education is an effort to mature humans who have an identity as actual human. School order is often used as an indication of the success of mental development and student behavior. The reality is that in schools there are stillmany violations of regulations school order. This condition gives rise to various problems and problems regarding implementation of moral education. This research uses Max Weber's social action theory with qualitative research methods and Schutz's phenomenological approach. Selection technique research subjects used purposive techniques. Data collection techniques are carried out through observation, interviews and documentation. Data analysis techniques use data reduction techniques, presenting data and drawing conclusions. The results obtained are the practice of school rules as a means of moral education at SMKN 3 Payakumbuh using a points system per semester recorded in the disciplinary book. Sanctions are educational in nature, especially for instilling students moral education. Enforcement of school rules at SMKN 3 Payakumbuh uses steps – steps in the form of installation in strategic places, socialization of school rules and regulations, and daily control of students as well as the involvement of teachers and leadership elements in maintaining social balance in the school environment. The obstacles faced in enforcing school rules are: lack of consistency of teachers in enforcing school rules. Efforts to overcome violations of school rules, namely preventive, curative and repressive measures.